Occurrence and distribution of soil Fusarium species under wheat crop in zero tillage - Silvestro, Luciana Belén; Steinglein, Sebastian Alberto; Forjan, Horacio Jose; Dinolfo, María Inés; Arambarri, Angélica Margarita; Manso, Marina Lucrecia; Moreno, María Virginia (2017)
The presence of Fusarium species in cultivated soils is commonly associated with plant debris and plant roots. Fusarium species are also soil saprophytes. The aim of this study was to examine the occurrence and distribution of soil Fusarium spp. at different soil depths in a zero tillage system after the wheat was harvested. Soil samples were obtained at three depths (0-5 cm, 5-10 cm and 10-20 cm) from five crop rotations: I, conservationist agriculture (wheatsorghum-soybean); II, mixed agriculture/livestock with pastures, without using winter or summer forages (wheatsorghum- soybean-canola-pastures); III, winter agriculture in depth limited soils (wheat-canola-barley-late soybean); IV, mixed with annual forage (wheat-oat/Vicia-sunflower); V, intensive agriculture (wheat-barley-canola, with alternation of soybean or late soybean). One hundred twenty two isolates of Fusarium were obtained and identified as F. equiseti, F. merismoides, F. oxysporum, F. scirpi and F. solani. The most prevalent species was F. oxysporum, which was observed in all sequences and depths. The Tukey’s test showed that the relative frequency of F. oxysporum under intensive agricultural management was higher than in mixed traditional ones. The first 5 cm of soil showed statistically significant differences (p = 0.05) with respect to 5-10 cm and 10-20 cm depths. The ANOVA test for the relative frequency of the other species as F. equiseti, F. merismoides, F. scirpi and F. solani, did not show statistically significant differences (p ≤ 0.05). We did not find significant differences (p ≤ 0.05) in the effect of crop rotations and depth on Shannon, Simpson indexes and species richness. Therefore we conclude that the different sequences and the sampling depth did not affect the alpha diversity of Fusarium community in this system.